Antibacterial Activity, Antioxidant and Phenolic Compounds of Honeys Produced by Nannotrigona testaceicornis Lepeletier (Apidae, Meliponini) (Research, Society and Development, 2021)
Bee honey is used in folk medicine to treat infections and oxidative damage. The composition of honey is quite variable, as it depends on the type of nectar of the plant species, the species of bee that produces it, the environmental conditions, collection and processing. This study aimed to evaluate the antibacterial and antioxidant activity, the content of total phenolic compounds and total flavonoids in honey from Nannotrigona testaceicornis L. The antibacterial activity was performed by the disk diffusion method and by the minimum inhibitory concentration. The antioxidant capacity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl free radical scavenging assay. The content of total phenols and flavonoids was quantified by spectrophotometry. It was observed that honey samples from May and June/2013 inhibited bacterial growth for all analyzed bacteria (Pseudomonas aeruginosa, Escherichia coli; Micrococcus luteus and Staphylococcus aureus). The ANOVA test showed that there was a statistically significant difference between months for P. aeruginosa; E. coli; M. luteus and S. aureus. In the assay to determine the minimum inhibitory concentration, samples from May/2013, March/2014 and June/2014 were more active against M. luteus. Antioxidant capacity above 60% was observed in the sample from May/2013. The samples from January/2014 and May/2103 stood out in the quantification of total phenols and total flavonoids, respectively. There was a positive correlation between antioxidant action and total flavonoids. Honey in natura from Nannotrigona testaceicornis L. showed antimicrobial potential and free radical scavenging capacity.